Moving into a new area to initiate fodder bank establishment - Suleiman, H.; Danbaba, M.M. (International Livestock Centre for Africa, 1984)
Presents and discusses an approach to establishing fodder banks. Discusses the two conditions that the farmers has to meet for participating in the programme. Ends with problems and observations.